Microbial contamination in a pediatric surgery operation theatre: Microbial contamination in theatre (Journal of Fatima Jinnah Medical University, 2020)
Background: In surgical patients, 38% of nosocomial/ health care associated infections are surgical site infections (SSI). The exogenous causes of SSI include microbial contamination of operation theatre environment, equipment, and personnel. The objective of this study was to generate local data involving microbial contamination of operation theatre environment, equipment, and personnel.Methods: This cross sectional survey was conducted in Pediatric Surgery Operation Theatre, Mayo Hospital, Lahore from August 2018 to September 2018. Samples for bacterial culture were taken by theatre sister and list in charge using cotton swabs moistened in normal saline. After informed consent, 53 samples were taken from the dominant hand and anterior nares of theatre staff (surgeons, nurses, theatre assistants and anesthetists), and 33 samples from operation theatre equipment and environment (laryngoscope, anesthesia machine, operation table, wall and floor of the theatre, dirty area, and store.). Air samples were collected by night staff using settle plate method on blood agar. After collection, all samples were transported to laboratory within 15 minutes, where pathologist performed antimicrobial susceptibility testing for all bacterial isolates using the Kirby-Bauer disc diffusion method.Results: This study had 24 (45%) of the samples from anterior nares, and 29 (55%) samples from dominant hand, while 33 samples were taken from theatre environment and equipment. Positive bacterial growth from theatre staff was seen in 9 (17%) out of 53 collected samples. Staphylococcus aureus was present in 5 (55.6%) of these 9 samples, while Staphylococcus epidermidis was present in 3 (33.3%), and 1 (11.1%) sample revealed Escherichia coli. In samples from operation theatre environment and equipment, 11 samples (33.3%) out of 33 samples had bacterial growth. Most common growth obtained was bacillus species (90.9%) either alone or as mixed growth, while 1 (9.1%) was Staphylococcus aureus.Conclusion: Despite observing standard protocols of theatre sterilization, microbial contamination was noted in 33.3% of samples collected from theatre and 17% from personnel. The main microorganism isolated from theatre environment and equipment’ samples was Bacillus (90.9%), and Staphylococcus aureus (55.6%) from theatre personnel.
Keywords: Microbial contamination; Operation theatre; Nosocomial infection; Health care associated infection; Surgical site infection